2013
DOI: 10.1080/09649069.2013.800290
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating decision-making by people with dementia: is spousal support gendered?

Abstract: The Mental Capacity Act 2005 clarifies the decision-making rights of people lacking capacity (such as people with dementia) and requires that carers and professionals support the individual in making decisions. This paper reports key findings from a qualitative study in England which examined the social process of everyday decisionmaking by couples living with dementia. The author identifies the various support strategies used by spouses when seeking to facilitate decision-making by their partners with dementi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 47 publications
1
33
0
2
Order By: Relevance
“…However, the overall study showed that carer-spouses did not always involve their partners with dementia in major decision-making processes (such as whether to attend a day centre or designate financial authority). Whilst this lack of involvement seemed to be explained, in the main, by the presence of significant speech impairment that would have made decision-making more challenging, it was not necessarily appropriate in terms of capacity, as the people with dementia often retained the ability to make these decisions (Boyle 2013b). Indeed, the same Act states that decisions should only be made on someone's behalf when they lack the capacity to make these decisions themselves.…”
Section: Deliberative Agency and Equalitymentioning
confidence: 89%
“…However, the overall study showed that carer-spouses did not always involve their partners with dementia in major decision-making processes (such as whether to attend a day centre or designate financial authority). Whilst this lack of involvement seemed to be explained, in the main, by the presence of significant speech impairment that would have made decision-making more challenging, it was not necessarily appropriate in terms of capacity, as the people with dementia often retained the ability to make these decisions (Boyle 2013b). Indeed, the same Act states that decisions should only be made on someone's behalf when they lack the capacity to make these decisions themselves.…”
Section: Deliberative Agency and Equalitymentioning
confidence: 89%
“…«Agency» handler om evnen til å uttrykke seg, enten gjennom verbale uttrykk eller kroppsspråk, og knyttes ofte til egenskaper ved individet. For personer med demens kan «agency» vaere kroppslig og habituelt forankret (Boyle, 2013(Boyle, , 2014Kontos, Grigorovich, Kontos og Miller, 2016). Anerkjennelse (recognition) handler om at mennesker har en iboende verdi som må respekteres for at medborgerskap skal bli realisert.…”
Section: Medborgerskap Praksiser Og Praxiografiunclassified
“…Most partners or adult children providing long-term support for someone living with dementia will experience relational and role change (Dunham & Cannon, 2008;Boylestein & Hayes, 2012;Toepfer et al, 2014) whereby they will eventually see themselves as a carer or caregiver -and these dynamics are often experienced differently for women and men (Carter et al, 2012;Boylestein & Hayes, 2012;Baker & Robertson, 2008;Friedmann & Buckwalter, 2014;Eriksson et al, 2013;Hayes et al, 2010;Russell, 2007;Calasanti & King, 2007;Dunkle et al, 2014). While husbands appeared to find it more challenging to adapt to taking on new daily household tasks, such as taking on the role of being the food provider (Russell, 2007;Boyle, 2013;Fjellström et al, 2010), adding to their stress as a caregiver, they were more likely to ask for help to perform these tasks (Sun et al, 2008), and have more informal help (Brown et al, 2007;Forbes et al, 2008). Women were reported to be more prepared to take on additional gendered tasks, and it was often viewed as a gradual extension of their existing work within their household (Calasanti & Bowen, 2006).…”
Section: Roles and Identitiesmentioning
confidence: 99%